Femoral and tibial stress fractures associated with vitamin D insufficiency. Issue 1 (26th June 2013) - Inklebarger, James; Griffin, M; Taylor, M J D; Dembry, R B
Abstract : We describe a case highlighting the need to consider hypovitaminosis-D when investigating background causation and treatment of femoral and tibial stress fractures. The case also suggests that prescribing calcium and vitamin D supplementation may help with fracture healing in soldiers presenting with stress fractures who may have unrecognised hypovitaminosis-D which if left untreated may delay fracture healing.